Comprehensive dialectical behavior therapy for adolescents in a juvenile correctional treatment center: a pilot evaluation - Folk, Johanna B.; Yang, Phillip; Thomas, Anne; Lyon, Jayme; Patel, Jaisal; Yoon, Clara; Robles-Ramamurthy, Barbara (Frontiers in Child and Adolescent Psychiatry, 2023)
Background: Incarcerated youth commonly present with emotion dysregulation, aggression, and comorbid psychiatric disorders, yet often do not receive necessary mental health treatment while confined. It is therefore crucial to expand the evidence base regarding empirically supported mental health interventions which are feasible to implement in secure settings to address incarcerated youth’s mental health needs. Through a community-academic partnership, the current pilot study evaluated a comprehensive Dialectical Behavior Therapy program implemented in a juvenile correctional treatment center. Methods: Youth participants (N=113) were on average 15.37 years old (SD=1.10, range=13-17), 68.1% boys, and identified as 69.0% Latinx, 22.1% Black, 8.0% White, and 0.9% Native American. Youth received comprehensive Dialectical Behavior Therapy for Adolescents (DBT-A), including individual therapy, skills training groups, family therapy, multi-family skills training groups, and skills coaching in the milieu by direct care staff who participated in extensive training and ongoing consultation team meetings. As part of a facility-designed program evaluation, youth completed a battery of empirically validated assessments of mental health and emotion regulation prior to and following completion of the program. Results: Results show that comprehensive DBT-A is feasible to implement in a juvenile correctional treatment center and overall, youth improved from pre- to post-treatment in mental health symptoms and emotion regulation, with small to medium effect sizes. Conclusion: These findings build upon a growing literature showing Dialectical Behavior Therapy is a promising intervention for treating emotion dysregulation and mental health conditions and can be successfully implemented in juvenile forensic settings.